An Echocardiographic Evaluation of Cardiopulmonary Evaluation of Cardiopulmonary Functions in Patients with Cirrhosis of Liver and Correlation with Severity of Disease - Panthi, Hari Prasad; Koirala, Dinesh; Pathak, Rahul; Bhandari, Brindeswari Kafle; Jha, Anurag; Hamal, Rabin; Bhusal, Mohan; Lamsal, Manoj; Gyawali, Susmita (Journal of Advances in Internal Medicine, 2023)
BACKGROUND Cirrhosis is the end result of varieties of chronic liver disease. A large proportion of patients with cirrhosis develop cardiopulmonary complication. The aim of this study was to evaluate the cardiopulmonary functions of patient with cirrhosis of liver and to correlate these abnormalities with CTP and MELD score. METHODS The study involved 81 cirrhotic patients admitted in Department of Gastroenterology of TUTH over a period of one year. The diagnosis of cirrhosis was established and clinical evaluation and investigation done. RESULTS The mean age of cirrhotic patients included in the study was 52 years. Alcohol was most common cause of cirrhosis (75.31%). The mean CTP score and MELD score was 10.02±1.77 and 23.59±7.53 respectively. Thirty patients (37.03%) had prolonged QTc interval, which had statistically significant association with alcohol as etiology of cirrhosis (p = 0.04). More than half (50.62%) of patients had diastolic dysfunction but it was not statistically significantly associated with CTP and MELD-Na score. Seven patients had evidence of intrapulmonary shunting, which had statistically significant association with MELD-Na score (p =0.01). Similarly, total 5 patients (6.17%) had PPHTN but there was no statistically significant association with CTP and MELD-Na score. Seventeen patients had dilated left atrium with no statistically significant association with CTP score and MELD-Na score. CONCLUSION There was significant incidence of cardiopulmonary abnormalities in cirrhotic patients. Every patient with decompensated cirrhosis irrespective of severity of disease should be evaluated for cardiopulmonary complication with a noninvasive, real-time, rapid imaging transthoracic contrast echocardiography.